2021
DOI: 10.1097/olq.0000000000001385
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the SARS-CoV-2 Pandemic on Human Immunodeficiency Virus and Bacterial Sexually Transmitted Infection Testing and Diagnosis in Oregon

Abstract: Human immunodeficiency virus, Neisseria gonorrhoeae/ Chlamydia trachomatis, and syphilis testing decreased with the implementation of mitigation measures for SARS-CoV-2 and did not return to 2019 levels by September 2020. However, primary and secondary syphilis diagnoses increased during mitigation measures. Sexual health services are essential during the SARS-CoV-2 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…Similar decreases in reported STIs during stay at home orders have been observed in other jurisdictions in the United States, 17 – 19 and the COVID-19 pandemic has impacted every aspect of STI diagnosis and control, including public health practices. Although King County typically has a robust behavioral surveillance framework in place, as in many other jurisdictions, 11 PHSKC staff deployments to the COVID-19 response impacted the completion of partner services interviews for STI cases.…”
Section: Discussionsupporting
confidence: 64%
“…Similar decreases in reported STIs during stay at home orders have been observed in other jurisdictions in the United States, 17 – 19 and the COVID-19 pandemic has impacted every aspect of STI diagnosis and control, including public health practices. Although King County typically has a robust behavioral surveillance framework in place, as in many other jurisdictions, 11 PHSKC staff deployments to the COVID-19 response impacted the completion of partner services interviews for STI cases.…”
Section: Discussionsupporting
confidence: 64%
“…Data from Oregon showed similar trends over the first six months of the pandemic, although testing slightly rebounded after the initial 2, 3 pandemic months. 13 During Oregon's stay-at-home order (March through May 2020), HIV diagnoses decreased by 36%, but this was not a statistically significant difference compared to periods before or after. A study of the first 5, 6 months of the pandemic revealed decreased HIV testing in emergency department (ED) sites in Illinois.…”
Section: Introductionmentioning
confidence: 95%
“…However, increasing evidence suggests social isolation measures may result in decreased testing, treatment, and reporting of cases. 4 6 …”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence suggests social isolation measures may result in decreased testing, treatment, and reporting of cases. [4][5][6] Throughout the COVID-19 pandemic, the Maricopa County Public Health Department (MCDPH) STD Clinic has maintained sexual health services fully operational, including Monday through Friday in-person express STD testing and medical provider visits. To understand the effect of COVID-19 isolation measures on sexual health care utilization and case reporting, we analyzed temporal trends of STD clinic attendance and STD morbidity in Maricopa County in relation to the COVID-19 Arizona Stay-at-Home Order.…”
Section: Introductionmentioning
confidence: 99%